THE EFFECT OF MINERAL ELEMENTS ON THE GROWTH OF INDOOR PLANTS (World Bulletin of Public Health, 2025)
This study investigates the influence of mineral elements on the growth, physiological activity, and ornamental characteristics of indoor plants. With increasing urbanization and the growing need for green spaces, indoor plants play a crucial role in improving air quality, human well-being, and interior aesthetics. The research focuses on the comparative effects of organic and inorganic fertilizers—specifically Biogumus and Kemira Lux—on plant species such as ivy, begonia, petunia, and geranium under laboratory conditions. The study revealed that Biogumus improved soil fertility and promoted healthy vegetative growth, while Kemira Lux stimulated faster flowering and enhanced ornamental qualities. The results highlight the importance of balanced mineral nutrition in achieving sustainable growth and aesthetic development of indoor plants.